Development and Preliminary Verification of Reactor Shielding Design Code cosSHIELD of COSINE Code Package. (September 2017) - Hu, Ye; Chen, Yixue; Zhang, Bin; Sun, Yeshuai; Yu, Hui
Abstract: COre and System INtegrated Engine for design and analysis (COSINE), is an integrated nuclear engineering code package, which is developed by State Nuclear Power Software Development Center (SNPSDC) in China. Reactor radiation shielding is an indispensable part of nuclear power plant design. According to relevant regulations and guidance, and based on the discrete ordinate method, the reactor shielding design code cosSHIELD was developed and verified preliminary using TEKEDA and Kobayashi benchmark. The results show that cosSHIELD can solve the critical and stationary source problem very well, in addition mitigate the ray effects efficiently.